Cerebral tumor with hemi-dural enhancement as unique presentation of multiple myeloma: A case report - Rick H.G.J. van Lanen; Sandra M.H. Huijs; Alida A. Postma; Roel H.L. Haeren (Brain and Spine, 2024)
Introduction: Intracranial multiple myeloma (MM) is a rare manifestation of MM, a malignant plasma cell disorder that primarily affects bone marrow. Dural involvement in MM is even rarer and can manifest as a dural mass. We present a case of MM presenting as an intracranial dural tumor with primary hemi-dural involvement. Research question: This case report aims to investigate the clinical presentation, diagnostic challenges, and treatment approaches for intracranial multiple myeloma, with a focus on the extensive hemi-dural thickening and enhancement seen in this case. Material and methods: A 73-year-old male presented with progressive dysphasia and weakness. MRI revealed a solid left frontal mass with significant mass-effect. Hemi-dural thickening and enhancement was present along with invasion of the skull. The patient underwent surgical resection of the tumor with dural and bone reconstruction. Results: Histopathological examination confirmed MM diagnosis. Chemotherapy was started. Follow-up MRI showed complete tumor resection, but extensive hemi-dural thickening and enhancement persisted. Postoperative radiation therapy was considered. Discussion and conclusion: MM with primary dural involvement is rare and poses diagnostic challenges. Postoperative treatment involves chemotherapy, the role of surgery and radiotherapy is not established. The extensive hemi-dural thickening and enhancement observed in this case require further investigation, and a wait-and-scan policy was recommended instead of radiotherapy.